(untitled) (Research, Society and Development, 2020)
In this study, it is proposed to produce artifacts for the care of users with chronic skin lesions in primary health care (PHC). Research of an applied nature was undertaken, with a qualitative approach, with theoretical anchoring in principles of clinical management and systematized methodologically based on techniques and tools for experimenting with design. The analysis of the content produced integrates data from an integrative literature review and dialogues in focus groups, involving the multiprofessional PHC team. From this analysis, four thematic categories emerged, in which the respective artifacts produced are presented, with a view to qualifying care in PHC to users with chronic skin lesions: conceptual map, with graphic representation that allows an overview of the team’s duties; care algorithm to support clinical decisions, care monitoring and evaluation; briefing that brings together the main therapeutic procedures with minimal resources and / or the option of special coverages fundamental to clinical and social management; and registration structure for the use of standards for monitoring, evaluation and decision support in care actions. The research contributes to the implementation of clinical management principles in PHC services, as it favors the incorporation of evidence-based practices, as well as the orientation of shared and interprofessional clinical actions, based on the needs of users with chronic injuries of skin, and quality and safety standards, focusing on undertaking best practices for the user when meeting the service.